[Red House, Trinidad, Port of Spain] - (:unkn) unknown (My University, 2010)
Exterior view of the Red House located in Port of Spain, Trinidad.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; [1925]; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Windows--Trinidad and Tobago; Towers--Trinidad and Tobago; Hedges--Trinidad and Tobago; Palms--Trinidad and Tobago; Red House, The (Trinidad and Tobago); Parliament Building (Trinidad and Tobago)